PENGUTAN KARAKTER RELIGIUS SISWA MELALUI PENDEKATAN PEMBELAJARAN DEEP LEARNING DI TK MUTIARA WAWORADA - Asmiati; Mulyadi, Wahyu; Kaharuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to address the issue of low religious character building in early childhood at Mutiara Waworada Kindergarten, where some students are unable to consistently demonstrate religious behavior, such as reciting prayers correctly, participating in worship activities in an orderly manner, and behaving politely in daily interactions. This condition requires a learning approach that is not only instructional but also able to guide children to a deep understanding of religious values. Therefore, this study aims to describe the process and impact of applying a deep learning approach in strengthening students' religious character, particularly in terms of spiritual, social, and emotional independence. This study uses a qualitative research type with a descriptive design. The data sources consist of classroom teachers, students in group B, and supporting documents in the form of lesson plans, observation notes, and documentation of learning activities. Data collection techniques include participatory observation, semi-structured interviews, and documentation of religious learning activities. The data was analyzed through stages of reduction, data presentation, and conclusion drawing by applying triangulation techniques to improve validity. The results of the study show that the application of the deep learning approach through worship observation activities, gradual guidance, simple reflection, and positive reinforcement succeeded in forming more consistent religious behavior in students. Children showed improvement in prayer discipline, emotional control, concern for friends, and independence in performing worship practices. Deep learning has been proven to have a holistic impact in strengthening religious character integrated with children's social and emotional development.